STRUKTUR DAN FUNGSI SOSIAL CERITA RAKYAT MAK LEKOH DI NAGARI KOTO BARU KECAMATAN KUBUNG KABUPATEN SOLOK - Islaminata, Dori; Hayati, Yenni; Nasution, Bakhtaruddin (Jurnal Bahasa dan Sastra, 2017)
This research purposed to describe: (1) The structure of foklore titled Mak Lekoh at Nagari Koto Baru, Kubung , Solok district, (2) The social function of foklore Mak Lekoh  at Nagari Koto Baru, Kubung , Solok district. The type of this research is qualitative research that using descriptive methode. The data collected by interview, recorded , transcription, transliteration, and clasification by recording result of inerview with an informan at Nagari Koto Baru, Kubung , Solok district. Analyzing data do with some steps. First, Inventaritation. Second, analysis. Third, data interpretation. Fourth, make a conclusion based on research result. Based on the research result, can be concluded these things. First, the structure of foklore Mak Lekoh  at Nagari Koto Baru, Kubung , Solok district covered: (a). Characterization, consist of two characters, they are the main character and additional character. The main character is Junaidi Dt. Panjang or Mak Lekoh , as known as a man who has a weirdness, when he died he become a tiger or become an mystic animal. In addition, the additional characters are his wife, childrens, his family and the civillians. (b). The plot of Mak Lekoh foklore shown  a conventional plot because it was regularly event trough the caused and effect , (c) Background,  it was at Nagari Koto Baru, Kubung , Solok district at long time ago placed in Lansanak area. (d). Theme, the theme is a certain life’s  point of view or certain felling that build a basic or main ideas  of literary work. Second, the social function of Mak Lekoh foklore as teaching , legation, self – identity , entertaining , and tradition function.Keywords: structure, social function, folklore